Tunable metasurface-based waveplates - A proposal using inverse design - Mohammadi Estakhri, Nasim; Engheta, Nader (Comptes Rendus. Physique, 2021)
An approach to achieve tunable free-space waveplate operation based on a two-layer cascaded metastructure is proposed. Phase retardation is varied through changing the axial distance between the two layers. Full control on the ellipticity of the output wave is attained with wavelength-scale variations in the axial distance. The theoretically desired characteristics of the metastructures are presented and multiple physical implementations are suggested based on inverse design topology optimization.